TOGA HATI: Improving community knowledge and behavior for hypertension prevention - Nita Pujianti; Ayu Riana Sari Azwari; Mohammad Bakhriansyah; Endah Labati; Muhammad Fahriza Firdaus; Renia Nor Azzahra; Isma Azizah; Riniarti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
Hypertension is one of the leading causes of premature mortality and remains a public health concern. High salt intake, insufficient physical activity, and the underutilization of medicinal plants (TOGA) contribute to the high prevalence of hypertension in West Mandikapau Village, Banjar Regency. This community service program aimed to improve knowledge and preventive measures related to hypertension through health education and medicinal plants utilization. Activities involved health cadres, PKK members, village officials, and local residents through hypertension education, healthy lifestyle promotion, demonstrations on processing medicinal plants such as celery, turmeric, ginger, and lemongrass, and the distribution of medicinal plant seeds for household cultivation. The program applied a participatory community-based approach involving PKK members as partners. The results showed improvements in participants’ knowledge, attitudes, and behaviors regarding hypertension prevention. The mean knowledge score increased from 72.6 to 96.2, the attitude score increased from 4.2 to 4.9, and the behavior score increased from 4.2 to 4.6. In addition, 78 percent of participants replicated household-level medicinal plants cultivation after the program. The integration of healthy lifestyle education and household-level medicinal plants utilization strengthened community participation, practical skills, and community self-reliance in sustainable hypertension prevention.